International liability arising from violations by Drones of the rules and principles of international humanitarian law . (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The rapid development in the field of information and communication technology has led to the emergence of new types of military weapons systems on the international scene. At the forefront are Drones that are electronically controlled remotely by individuals or using artificial intelligence. With the increase in scientific and technological progress that the world has witnessed in recent years, countries especially developed ones, are seeking to develop their military and security capabilities and strengthen their deterrence mechanisms by possessing this type of aircraft due to its capabilities and superiority in the military aspect. Although drones constituted a scientific qualitative shift in the history of humanity, their hostile employment in military conflicts and the expansion of their use by states during contemporary armed conflicts as a hidden weapons and an effective tool for espionage and military and logistical action in the main points of conflict in the world were accompainied by clear violations of the prorisions of the law. International law in general, such as the necessity of respecting the sovereignty of states and not interfering in the internal affairs of other states. And international humanitarian law in particular, such as unlawful attacks on civilians and civilian objects. The raises the issue of wheather or not the international criminal and civil responsibility of the state violating the rules and principles of international humanitarian law is based on its use of drones .